Pengaruh Penambahan Pasir Pantai terhadap Laju Kenaikan Kuat Tekan beton - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Teknik Mesin Fak. Teknik UGM, 2003)
The strength of ordinary concrete at 28 days of age is referred to as 100% and still increases asymtotically with age. Long-term strength decreases due to corrossive environment. The purpose of the research was to know the rate of strength of concrete using additional seashore sand (SS) in comparison to the ordinary sand (OS) as the fine agregate. The experiment used fine aggregate from Alam lndah Seashore, from Gung River while the coarse aggregate from Prupuk, Tegal, Central-Java. The Portland Pozzoland Cement (PPC) was used for all mix types. To monitor the rate of strength the mix design of concrete was established with water cement ratio (w/c) of 0,5 and cement content (cc) of 400 kg/m . From the investigation it was found that the seashore sand and river sand had respectively the fineness modulus of 1,23 and of 3,19